Proposta de um método para auxiliar na definição de uma diretriz estratégica da qualidade - Silveira, Cícero Giordani da (Universidade do Vale do Rio dos Sinos, 2011)
In the industrial environment, the pursuit of excellence with permanent and continuous improvement makes the Quality Management Systems find themselves in constant evolution. The Quality Management Systems give support for the manufacturing of products which meet customers? expectations at competitive costs. The quality of the products manufactured can contribute significantly to the performance and financial results of an organization. Quality problems, being them detected within the company or by the client, can generate high costs. Besides the financial cost, quality problems can generate intangible losses, such as, loss of customer, destruction of company image and brand credibility. Problems with product quality can also cause delivery problems and losses due to reduced productivity of the company or client. With the goal of improving the performance of quality reducing scrap, rework, returns and unnecessary inspections, comes the need to establish a strategic guideline of quality. There are several tools and management practices which seek to improve the quality of the product. Among several options available, organizations can determine which tools will be used in their quality strategy. Through a survey, mostly qualitative, this paper aims to present a proposal for a method to assist manufacturing companies in setting a strategic guideline aimed at improving the quality of the product quality and reduction of quality costs. To support this study studied the evolution that the quality systems had over time, the basis of strategic quality management, the costs of poor quality and the main tools used by manufacturing companies to face failures, reduce costs and improve the level of product quality. Then, a method was developed to assist companies in setting a strategic guideline of quality. The proposed method was applied in a company in the metal-mechanic sector in order to test it and feed it back with improvements from practical application. The results were analyzed and based on the learning gained by experience; this method has been reformulated to incorporate the improvements generated by the practical application. This paper leaves as a contribution the proposal of a method with 14 steps which can be used by companies from several sectors to assist in defining its strategic guideline of quality when it is focused on improving product quality and reducing the costs of poor quality.
Keywords: Sistema de gestão da qualidade; Estratégia de qualidade; Ferramentas da qualidade; Custos da qualidade; Quality management system; Quality strategy; Quality tools; Costs of quality; ACCNPQ::Engenharias::Engenharia de Produção